Early Parenthood Experiences in Davao City, Philippines - Aperocho, Maico Demi; Estampador, Jane; Serafica, Jhelaica; Villegas, Jana (International Journal of Qualitative Research, 2023)
This study explored the experiences of young mothers in early parenthood. This qualitative study was conducted using the phenomenological method. The seven participants were purposively selected to be interviewed. The data analysis results reveal interesting themes regarding the mothers’ experiences, challenges, coping strategies, and insights during early parenthood. Themes for experiences such as dilemma in providing proper care, feelings of apprehension and shame, failed expectations, society’s judgment, satisfying feeling of achieving motherhood, and lack of time for self are revealed in experiences. Mothers in early parenthood experienced challenges such as being financially incapable, mentally and emotionally unprepared, and unprivileged to finish school. Finding strength from family and God, using personal strategies, and getting support and motivation from the husband are the coping strategies of mothers when dealing with challenges. The mothers’ insights include being prepared for the consequences, parents knowing what is best for us, being a mother is a big shoe to fill, and weighing things wisely. The gathered data from the participants will provide invaluable insights and knowledge that can contribute to the field of social work by strengthening prevention efforts. In addition, by understanding young parents' unique experiences and needs, social workers can develop effective programs and services to help address their challenges. Finally, the younger generation may get a significant takeaway from the study about the experiences and consequences of early parenthood.